Evaluation of an Aqueous Extract from Horseradish Root (Armoracia rusticana Radix) against Lipopolysaccharide-Induced Cellular Inflammation Reaction. (15th January 2017) - Herz, Corinna; Tran, Hoai Thi Thu; Márton, Melinda-Rita; Maul, Ronald; Baldermann, Susanne; Schreiner, Monika; Lamy, Evelyn
Abstract : Horseradish ( Armoracia rusticana ) is a perennial crop and its root is used in condiments. Traditionally, horseradish root is used to treat bacterial infections of the respiratory tract and urinary bladder. The antiphlogistic activity, determined in activated primary human peripheral blood mononuclear cells (PBMC), was evaluated for an aqueous extract and its subfractions, separated by HPLC. Compound analysis was done by UHPLC-QToF/MS and GC-MS. The aqueous extract concentration-dependently inhibited the anti-inflammatory response to lipopolysaccharide (LPS) in terms of TNF- α release at ≥37 μ g/mL. Further, the cyclooxygenase as well as lipoxygenase pathway was blocked by the extract as demonstrated by inhibition of COX-2 protein expression and PGE2 synthesis at ≥4 μ g/mL and leukotriene LTB4 release. Mechanistic studies revealed that inhibition of ERK1/2 and c-Jun activation preceded COX-2 suppression upon plant extract treatment in the presence of LPS. Chemical analysis identified target compounds with a medium polarity as relevant for the observed bioactivity. Importantly, allyl isothiocyanate, which is quite well known for its anti-inflammatory capacity and as the principal pungent constituent in horseradish roots, was not relevant for the observations. The results suggest that horseradish root exerts an antiphlogistic activity in human immune cells by regulation of the COX and LOX pathway via MAPK signalling.